Genu Sinistra Tuberculosis Arthritis with Drug-Induced Liver Injury Caused by Anti-Tuberculosis Drugs in Patients Confirmed with COVID-19 - Yonis Ismed; Radiyati Umi Partan (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: Tuberculous arthritis is a form of extrapulmonary tuberculosis and has a significant effect on patient morbidity and mortality. This case report aims to describe clinical signs and symptoms, results of laboratory tests, radiology, and outcome of tuberculosis arthritis cases. Case presentation: A 36-year-old woman came to the emergency room with the main complaint of pain, swelling, and warmth when palpating the knee for the past week. The pain felt worse during activities such as walking. The patient also complains of fever, loss of appetite, and unwanted weight loss. Physical examination showed sharp pain and swelling in the knee, limited range of movement (ROM), and a positive balloon sign, while laboratory tests showed increased leukocytes, neutrophils, and C-reactive protein. After the diagnosis of genu tuberculosis arthritis was established, the administration of anti-tuberculosis drugs (OAT) was started. After one week, the patient complained of pain in the left knee and progressive nausea. Liver function tests showed an increase in SGOT and SGPT. The patient then started OAT desensitization. A month later, the patient underwent an open synovectomy with liquefaction necrosis. Although the first desensitization of tuberculosis still causes drug-induced liver injury, the second desensitization involves gradually increasing doses of rifampicin accompanied by close monitoring of liver tests. Conclusion: Early administration of anti-tuberculosis drugs in tuberculosis arthritis can improve healing, maintain joint function, and prevent further damage. Anti-tuberculosis drug desensitization is the primary management of drug-induced liver injury.